1979
DOI: 10.4294/jpe1952.27.497
|View full text |Cite
|
Sign up to set email alerts
|

Seismic refraction and reflection measurements around Hokkaido. 2. Crustal structure of the continental slope off Hidaka.

Abstract: Refraction measurements by the two ship method were conducted in July 1969 in the deep sea terrace of Hidaka , Hokkaido. The general features of the crustal structures derived are similar to those in the adjacent oceanic areas. Thick sediments cover the whole area, especially its northernmost part. The layer with a P-wave velocity of 6km/s is found in all profiles. That is, the crustal structure in this area is continental and similar to that off the Sanriku area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Relation between P-wave Velocity Structure and the Urakawa-oki Earthquake P-wave velocity structure beneath Hidaka mountains and off Urakawa region have been studied by ASANO et al (1979), DEN and HOTTA (1973), FUJII and MORIYA (1983), MORIYA (1984), andTAKANAMI (1982). DEN and HOTTA (1973) and ASANO et al (1979) found a thick sedimentary layer of 10-17 km with a velocity of 4.2 km/s beneath the continental slope off Urakawa by refraction and reflection experiments. FUJII and MORIYA (1983), through travel-time analysis of the refracted waves from the quarry blasts in the central part of Hidaka mountains, found that sedimentary layers of 3.6 km/s and 4.7 km/s become thick stepwise along the west side of Hidaka mountains reaching a depth of 9 km beneath the coastal region of Hidaka.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relation between P-wave Velocity Structure and the Urakawa-oki Earthquake P-wave velocity structure beneath Hidaka mountains and off Urakawa region have been studied by ASANO et al (1979), DEN and HOTTA (1973), FUJII and MORIYA (1983), MORIYA (1984), andTAKANAMI (1982). DEN and HOTTA (1973) and ASANO et al (1979) found a thick sedimentary layer of 10-17 km with a velocity of 4.2 km/s beneath the continental slope off Urakawa by refraction and reflection experiments. FUJII and MORIYA (1983), through travel-time analysis of the refracted waves from the quarry blasts in the central part of Hidaka mountains, found that sedimentary layers of 3.6 km/s and 4.7 km/s become thick stepwise along the west side of Hidaka mountains reaching a depth of 9 km beneath the coastal region of Hidaka.…”
mentioning
confidence: 99%
“…A pair of arrows denotes the fault motion of the mainshock. The inserted figure shows studied area and measurement lines used to compile the structure: A, the aftershock area by MORIYA et al (1983); B , the area in the square studied by MIYAMACHI and MORIYA (1984) using three-dimensional inversion method and observation area of the quarry blasts by FUJII and MORIYA (1983); D , refraction and reflection measurement lines after DEN and HOTTA (1973) and ASANO et al (1979). Focal mechanism solution in the inserted figure (equal area projection of the lower hemisphere) after MORIYA et al (1983) is modified to reader's side hemisphere projection in the main figure.…”
mentioning
confidence: 99%
“…The geology offshore of northeast Japan is not well known. Interpretations of drilling (von Huene et al, 1982; Japan Association of Natural Gas, 1986), gravity data (Nishimura and Murakami, 1977;Nishimura et al, 1984), and seismic refraction and reflection data (Honza et al, 1978;Asano et al, 1979;von Huene et al, 1982;Suyehiro et al, 1990) suggest that the near-trench Pacific forearc consists ofNeogene and Quaternary forearc basin sedimentary rocks floored by a basement of Cretaceous sedimentary rocks.…”
Section: Geologymentioning
confidence: 99%
“…The RGES shown by solid line indicates the profile in the study of explosion seismology, which was conducted in 1968 and 1969 by the Japanese Research Group for Explosion Seismology (RGES) (OKADA et al, 1973). Profiles A-B, B-C, C-G, etc., in Hidaka trough show the locations of profiles of refraction measurements made by DEN and HOTIA (1973) and ASANO et al (1979).…”
mentioning
confidence: 99%